Heart rate variability and autonomic activity in young short-track athletes at the age of 14 - Brook T.M. ,; Litvin F.B. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the features of heart rate regulation and autonomic regulation for an orthostatic test in 14–year-old short-track athletes in the pre-competition training period. Methods and structure of the study. The study involved 22 young male short-track athletes, with an average age of 14 years. The experiment was conducted at the stage of preparation for the competition. Temporal (MxDMn, RMSSD, SI) and spectral (TP, HF, LF, VLF) parameters were recorded using the Varicard 2.51 complex and ISCIM-6 software. Further processing and study of the obtained data were carried out using mathematical statistics methods. Results and conclusions. For fourteen-year-old short-track athletes, the average values of temporal and spectral parameters in the clinostasis position significantly exceed the standard values typical for their peers who do not engage in sports. These values are also significantly higher than those of young athletes of the same age who specialize in other disciplines. The analysis of vegetative reactivity using an orthostatic test showed the presence of an overactive reaction of the body to a change in body position.